Differentially Expressed Circular RNA Profile Signatures Identified in Prolificacy Trait of Yunshang Black Goat Ovary at Estrus Cycle - Liu, Yufang; Zhou, Zuyang; He, Xiaoyun; Jiang, Yanting; Ouyang, Yina; Hong, Qionghua; Chu, Mingxing (Frontiers in Physiology, 2022)
CircRNAs acting as miRNA sponges play important roles in the growth process of animal individuals. The prolificacy trait of goats is involved in many pathways, however, the variation of circRNA expression profiles in the different phases of the estrus cycle at high and low fecundity groups is still unknown. Here, we analyzed the circRNA profiles of ovarian tissues among high and low fecundity groups in the follicular phase (HF vs LF), high and low fecundity groups in the luteal phase (HL vs LL), and high and low fecundity in the whole estrus cycle (HF vs HL and LF vs LL) using RNA-seq. A total of 283 (114 upregulated and 169 downregulated), 559 (299 upregulated and 260 downregulated), 449 (254 upregulated and 195 downregulated), and 314 (210 upregulated and 104 downregulated) differentially expressed (DE) circRNAs were screened in HF vs LF, HF vs HL, HL vs LL, and LF vs LL groups, respectively. Enrichment analysis suggested that the targeting of DE circRNAs was mainly enriched in oocyte meiosis, the GnRH signaling pathway, and estrogen signaling pathway. After integrating our previous study of miRNA-seq, there were 56 miRNAs that could target to 192 DE circRNAs, including the miR-133 family (including miR-133a-3p and miR-133b), miR-129-3p, and miR-21, which also had important influence on the prolificacy trait of goats. Then, 18 circRNAs with coding potential were obtained by four software predictions, and 9 circRNAs were validated by RT-qPCR. Together, circRNAs play a key role in the prolificacy trait and the transformation of the follicular phase to the luteal phase in the estrus cycle of goats.